Impact of Emo-Demo IYCF Education on Dietary Intake and Growth Indicators in Children Under Two in Rural Area - Mukaromah, Irdat; Widya Hapsari, Pramesthi; Sofiyya Wahyurin, Izka; Andini Surijati , Katri; Aryani, Aisyah A.; Proverawati, Atikah; Nurbaya, Nurbaya (Yayasan Mandar Indonesia, 2025)
Limited maternal knowledge of infant and young child feeding (IYCF) practices contributes to inadequate dietary intake and poor nutritional status among children under two years old. Emotional-Demonstration (Emo-Demo), an educational approach that combines practical demonstrations with emotional engagement, has shown promise in improving feeding behaviors. This study aimed to assess the effect of IYCF education using the Emo-Demo method on children’s energy intake and nutritional status. A quasi-experimental study with a one-group pretest–posttest design was conducted at the East Purwokerto I Health Center between May and August 2024. The intervention consisted of seven educational sessions. Energy intake was measured using a single 24-hour food recall, and nutritional status was assessed using weight-for-age z-scores (WAZ) obtained with a digital baby scale. A total of 18 mothers of children under two were recruited using purposive sampling. Paired t-tests were used for data analysis. Most mothers were aged 20–35 years (77.8%) and were housewives. The Emo-Demo intervention significantly increased mean energy intake (+239.6 ± 239.9 kcal/day, p<0.001, d=0.72) and improved WAZ scores (+0.23 ± 0.27, p=0.002, d=0.23), indicating positive effects on both dietary intake and nutritional status.